Testes de germinação e vigor em sementes de feijão irrigado - cultivar BRS FC402 - MARCONDES, Bruno Ruan Rossatti; LOPES, Adriano da Silva; MOREIRA, Júlia Neves; FRANCO, Jhonatan da Silva; MEDEIROS, Rodinei Domingos; KRAESKI, Marcos Jefferson (ANAIS DO ENIC, 2025)
-